GATA2 deficiency in an adult with alveolar proteinosis, infections, lymphadenopathy with granulomatosis, and immune deficiency: case report - Gabzdilová, Juliana; Raffáč, Štefan; Krasňanská, Gabriela; Konečný, Michal (Frontiers in Immunology, 2025)
GATA2 protein is an important hematopoietic transcription factor. GATA2 deficiency, caused by heterozygous mutation of GATA2, includes a group of diseases presented with monocytopenia, cellular immunodeficiency with marked susceptibility to infection (mycobacterial, fungal, and viral), myelodysplasia (MDS), leukemic transformation, vessel abnormalities, and deafness. Most data are available in case reports. The challenge is to increase the awareness about GATA2 deficiency and to find the best treatment protocol for the patient. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only curative treatment available. However, it is also associated with significant treatment-related morbidity and mortality. Therefore, determining the appropriate timing of allo-HSCT is critical. We present the case of a young adult man with severe lung alveolar proteinosis, granulomatous disease, infections, and autoimmune complications present before we confirm GATA2 as a newly described mutation. The main sign that led to the suspicion of GATA2 deficiency was prolonged monocytopenia and absence of monocyte in peripheral blood and bone marrow along with recurrent infections and alveolar proteinosis. The exact and early diagnosis of this disease is crucial. The late stage of the disease is associated with increased mortality and severe complications that contraindicate bone marrow transplantation or worsen survival. The clinical implication of this article is to improve awareness about the different clinical forms of GATA2 deficiency and the new mutations described in this field. Our aim is to share real-life experiences with disease development and treatment during the lifetime of a young patient.